2005
DOI: 10.1002/syn.20144
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic differences in the postmortem striatum of subjects with schizophrenia: A stereological ultrastructural analysis

Abstract: The striatum processes motor, cognitive, and limbic function, all of which are perturbed in schizophrenia. The present study examined the synaptic organization of the caudate and putamen in schizophrenia. Postmortem striatum was obtained from 10 normal controls (NC) and 17 subjects with schizophrenia (SZ), prepared for electron microscopy, and analyzed using stereological principles. The densities of total synapses, asymmetric synapses (characteristic of excitatory inputs), and asymmetric axospinous synapses (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 121 publications
(105 reference statements)
5
39
0
3
Order By: Relevance
“…This is consistent with findings in the dorsal striatum which also found an increase in AS synapses in SZ. 6 In agreement with this finding is evidence for an increased expression of the excitatory PSD protein SAP90/PSD-95-associated protein 1 (SAPAP1) in the NAcc in postmortem SZ. 23 Rodent models of SZ also exhibit increased indices of glutamatergic-type input in the NAcc; rats treated with psychotomimetics have increased mRNA expression of excitatory PSD genes, 23,24 and increased dendritic spine density in the NAcc, [25][26][27] which is tightly correlated with the density of AS synapses.…”
Section: Elevated Excitatory Input In Szsupporting
confidence: 72%
See 1 more Smart Citation
“…This is consistent with findings in the dorsal striatum which also found an increase in AS synapses in SZ. 6 In agreement with this finding is evidence for an increased expression of the excitatory PSD protein SAP90/PSD-95-associated protein 1 (SAPAP1) in the NAcc in postmortem SZ. 23 Rodent models of SZ also exhibit increased indices of glutamatergic-type input in the NAcc; rats treated with psychotomimetics have increased mRNA expression of excitatory PSD genes, 23,24 and increased dendritic spine density in the NAcc, [25][26][27] which is tightly correlated with the density of AS synapses.…”
Section: Elevated Excitatory Input In Szsupporting
confidence: 72%
“…Some of the control (n = 3) and SZ (n = 5) cases used in this study have also been used in previous studies analyzing synaptic density of the dorsal striatum. [5][6][7][8][9] Coronal blocks of the striatum were immersed in 4% paraformaldehyde and 1% glutaraldehyde in 0.1 M phosphate buffer for at least 1 week (4°C). Striatal tissue was then sectioned at a thickness of 40 µm with a Vibratome into 6 free-floating series.…”
Section: Brain Tissuementioning
confidence: 99%
“…Higher numbers of corticostriatal synapses were reported in the anterior caudate in schizophrenia (Roberts et al, 2005b). Alterations may differ between schizophrenia subtypes, with a higher density of excitatory inputs in striatal patches in schizophrenia, but increases in the matrix only in subjects with undifferentiated schizophrenia (Roberts et al, 2008).…”
Section: Snare Protein Levelsmentioning
confidence: 92%
“…Postmortem studies have identified structural features in the central nervous system (CNS) that are characteristic for many neurological syndromes and the approach is somewhat successful for certain psychiatric conditions, such as schizophrenia (Roberts et al, 2005;Rowland, 2005). Unfortunately, this analysis is applicable only to deceased individuals and it cannot be used in the initial diagnosis.…”
Section: Introductionmentioning
confidence: 99%